Struktur Frasa Verbal Bahasa Banjar Hulu: Tinjauan Bentuk Gramatikal - Asnawi, Asnawi (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2018)
The basis of the emergence of this research is the lack of observers or language researchers who will arouse the local language khasanah, namely Banjar Hulu language. Upstream Banjar Language is a language used by the people of Suhada Village Enok District Indragiri Hilir Regency Riau. The Banjar Hulu language is used as the majority language used by the people of Indragiri Hilir Regency Riau. However, due to the flow of modernization and assimilation will threaten the extinction and contamination of the Banjar Hulu language. Therefore, this research is expected to maintain and maintain the authenticity of Banjar Hulu language, so it is necessary to do research. This study focuses on the structure of verb phrases. With related issues about the shape or structure of the verb phrase. The purpose of the study is to describe in detail the structure of the Banjar Hulu language verb phrase. This research is a field research with qualitative type. This research was conducted in Suhada Village, Enok Sub-district, Indragiri Hilir Regency, Riau with research time for six months. The method used to collect data is by the technique of referring libat ably. The data of this research is phrase construction that comes from the speech of research informant. Data analyzing is done by technique of reduction, disply, and conclusion data. The results showed that there are various verbal phrases. This kevariasian found verbal language phrases Banjar Hulu language based on the class of formers and verbal phrase forming function, namely coordinative verbal phrases, modifikatif, and apositif. The results of this study are the first structure of verbal phrases based on the word class; (v) Verbal Phrase V + Ajk, (c) Verbal Phrases Adv + V, (d) Verbal Phrases V + Prepositions, (e) ) Verbal Phrases V; (ba- + N) + pronomina, (f) Verbal Phrases V; (b) + A, (g) Verbal Phrases V; (b + + N) + N. The two structures of the verbal phrase are based on the function of the constituent elements, which include (a) Coordinative Verbal Phrases, (b) Modifikattive Verb Phrases, (c) Apositive Verb Phrases.